IDENTIFIKASI POTENSI SARI BUAH JERUK MENJADI LISTRIK SEBAGAI SUMBER BELAJAR FISIKA MATERI ARUS LISTRIK SISWA SMP KELAS IX - ., Fitriyaningsih; ., Partono (UNIVERSITAS MUHAMMADIYAH METRO, 2014)
The purpose of this study was 1. To know potential of different citrus fruit juice varieties into electricity. 2. To know juice of citrus varieties that have the potential to be superior in electrical 3. To know piece of research that can be used as a learning resource. 4. To know learning resources that can be generated from the research. The place is a laboratory study was conducted of science, University of Muhammadiyah Metro May 25, 2014. Oranges juice were taken from five different varieties are citrus, lime, tangerine, grapefruit, and lime. There are three variations of existing experiments in the study of differences in varieties, differences in the distance between the electrodes, and the difference in volume. There are five treatments and five repetitions in this experiment. In the process the research data used ANOVA analysis of non-parametric Kruskal Wallis test. The experimental results showed that the juice that comes from different varieties have different potentials in into electricity. Lemon juice is the most superior varieties as electricity. Part of research that can be used as a learning resource that the pH value of each citrus varieties, the use of digital multitester, and the voltage generated. The results of this study can benefit as a learning resource in the form of worksheets.Â